Chemistry of pleasure - Zimmerman, Effie Jeannetta (My University, 1891)
Introduction: As pleasure is the brightest element in our life history it seems well to consider its composition, how obtained and how best effected. We study the chemistry of minerals and all important elements, and by so doing we obtain a more definite idea of what they are composed and of what value they can be to man. By such experiments elements have been combined and have produced most wonderfully imposed substances, much more important than the separate elements. In studying the chemistry of pleasure one must follow the same analysis and mode of operation as in analyzing substances. Pleasure may be divided into natural and artificial. The former surpasses all other in sublimity, it is that which startles us and awakens our inner self to realize a superior ruling being. It is constant in its effects and may be enjoyed equally by all. The little book warbles so sweet a tune to the little fisher boy as it does to the most royal of men. The birds sing as sweetly around the rudest of cottages as they do among the trees of the most elegant of places. The beautiful landscape spreads far away into the distance and inspires us to do greater deeds and more noble acts.
Citation: Zimmerman, Effie Jeannetta. Chemistry of pleasure. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Pleasure; Chemistry; Element; Balance; Earth; Theses; Manuscripts (documents)